TRANSFORMATION OF THE VALUE FOUNDATIONS OF CULTURE INFORMATION NETWORK SOCIETY - Nadezhda N. Isachenko (Russian Studies in Culture and Society)
In Russian humanitarian thought, the problems of preserving and further developing the spiritual, value component of human activity in the context of a developing information and network society are widely discussed. Informatization, digitalization, expanding the boundaries of the information and network space, constructively transforms human existence. Screen, network culture demonstrates qualitatively new approaches to understanding the phenomena of "culture", "values", "norms". The ideas propagated by virtual countercultures and subcultures aimed at the formation of utilitarian, hedonistic attitudes contribute to the leveling of ethical, moral principles, and the de-formation of a value system. This indicates that the dynamics of value bases is shifting from the highest to the lowest pole: from spiritual to material, from traditional to universal, from socially significant to individual values. The focus of this problem is to create a humanistically oriented environment filled with ethical imperatives and fundamental values.